Perbedaan Motivasi Dan Hasil Belajar Biologi Peserta Didik SMA Negeri 1 Makassar Antara Media Video Pembelajaran dengan Mobile Learning - Mulyati Mulyati; Firdaus Daud; Muhammad Danial (Universitas Negeri Makassar, 2022)
This article discusses the differences in learning motivation and learning outcomes of students at SMA Negeri 1 Makassar who are taught through video learning media and mobile learning. This research is a quasi-experimental research. The research design used is Non-equivalent control[1]group design. The variables in this study are the independent variables, namely video learning media and mobile learning, the dependent variable is learning motivation and student learning outcomes. Sampling in this study was done by random sampling technique. One class uses video learning media and the other class uses mobile learning. The results showed that there were significant differences in students' motivation and learning outcomes in classes taught through video learning media and mobile learning. The motivation and learning outcomes of students' biology showed that the class that used mobile learning showed an increase in motivation and better learning outcomes than the class that used video learning media. So it can be concluded that there are differences in the motivation and learning outcomes of biology students who are taught through video learning media and mobile learning in class XI MIPA SMA Negeri 1 Makassar.